Peri-tumor fibroblasts promote tumorigenesis and metastasis of hepatocellular carcinoma via Interleukin6/STAT3 signaling pathway - Zhao, Zhenxiong (Cancer Manag Res, 2019)
Purpose: Because many hepatocellular carcinoma (HCC) cases develop from fibrotic or cirrhotic livers, fibroblasts are abundant in the microenvironment of HCC. Although the contribution of cancer-associated fibroblasts (CAFs) to the progression of HCC is well established, the role of fibroblasts has not been comprehensively revealed. Patients and methods: The RayBio Human Cytokine Antibody Array was used to elucidate the role of peri-tumor fibroblasts (PTFs) in promoting malignant properties of HCC. IL-6 and STAT3 signaling were inhibited in both HCC cell lines and non-tumor L-02 liver cells to further determine its role in the progression of HCC. Moreover, the expression of IL-6 and pTyr705 STAT3 was detected in HCC samples and peri-tumor liver tissues by immunohistochemical staining. Results: PTFs not only promoted the proliferation, invasion, and metastasis of liver cancer cells, but also stimulated the permanent malignant transformation of human non-tumor L-02 liver cells, resulting in hepatocarcinogenesis in vivo. The RayBio Human Cytokine Antibody Array indicated that PTFs secreted a higher level of soluble IL-6 than CAFs. IL-6 derived from PTFs greatly activated STAT3 Tyr705 phosphorylation in both non-tumor L-02 cells and HCC cells. IL-6-neutralizing antibody and STAT3 Tyr705 phosphorylation inhibitor, cryptotanshinone, largely abolished the positive effects of PTFs on HCC carcinogenesis and progression. Moreover, high expression of pTyr705 STAT3 in peri-tumor tissues was significantly correlated with tumor recurrence rate after three years in a postsurgical follow-up with patients with HCC. Conclusion: These results indicated that PTFs induce carcinogenesis and development of HCC via IL-6 and STAT3 signaling.